Actos inseguros y su influencia en la accidentabilidad laboral en los trabajadores del área de producción de la empresa aserradero y ferretería Nelly y la elaboración de un plan de intervención basado en el comportamiento seguro. - Chiluisa Travez, Mariela Alejandra (2016)
This research work aims to publicize the results of research in the production area sawmill Nelly. The main objective of the research was to identify unsafe acts in labor accidents in the production area sawmill and hardware Nelly., The methodology used a quantitative approach, using for this modalities bibliographic and field research through as observation technique for video cameras, and direct observation and thus to know the different unsafe acts by workers during 2015. the results of this research products allow us to determine the main events that constantly performed by workers to perform their daily tasks, and relate the results and accident rates of 2015 to thereby apply an intervention plan based on safe behavior of people; this paper finally concludes that unsafe acts by the people indexed on labor accidents of workers and in turn the main cause is the lack of basic procedures and a lack of preventive culture within the company.